TINJAUAN YURIDIS KONTRAK PENGADAAN BARANG ATAU JASA PEMERINTAH DI KABUPATEN KETAPANG (Studi Kasus Pembangunan Rumah Staf Camat Singkup Pada Dinas Pekerjaan Umum Kabupaten Ketapang Kalimantan Barat) - , Muzia Amanda, SH, Dwi Haryati, S.H,.M.H ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research juridically aims to determine the implementation of the Contract for Procurement of the Government of Goods or Services based on Presidential Regulation No. 54 of 2010, to find the consequences of the occurrence of Default on Government Procurement of Goods or Services, and to know the government's guarantee of protection for the Procurement of Goods or Services. This research is the combination of empirical research and normative research. Empirical conducted by identifying and clarifying the implementation of the provisions of the legal regulations that applicable to the Contract for Procurement of Goods or Services, and normative conducted by examines the related provisions of Regulation Legislation (Bibliography). This research subsequently processed by using descriptive methods which is a descriptive research or to describe the facts of field research although library research. The results of this study are: (1) The contract of Government's Goods or Services Procurement for the Staff's housing constructions in the District of Ketapang is corresponding with the applicable Laws and Regulations